Disease Activity As a Major Determinant of Quality of Life and Physical Function in Patients With Early Axial Spondyloarthritis. Issue 1 (21st November 2016) - Fernández‐Carballido, Cristina; Navarro‐Compán, Victoria; Castillo‐Gallego, Concepción; Castro‐Villegas, Maria C.; Collantes‐Estévez, Eduardo; de Miguel, Eugenio; ,
Abstract : Objective: To describe health‐related quality of life (HRQOL) and physical function in patients with early axial spondyloarthritis (SpA) and to assess their associations with disease activity and radiographic damage. Methods: This was a cross‐sectional study drawing upon baseline data of axial SpA patients (Assessment of SpondyloArthritis international Society criteria) from the ESPERANZA cohort. Linear regression analyses were used to evaluate the associations between disease activity and radiographic damage (spine and sacroiliac joints) with HRQOL, physical function, and spinal mobility. Results: In total, 259 patients were included. The mean ± SD age was 32.2 ± 6.9 years, disease duration was 13.3 ± 6.8 months, Ankylosing Spondylitis Quality of Life score was 5.9 ± 4.8, Bath Ankylosing Spondylitis Functional Index score was 2.4 ± 2.3, Bath Ankylosing Spondylitis Metrology Index score was 1.4 ± 1.3, Bath Ankylosing Spondylitis Disease Activity Index (BASDAI) score was 3.8 ± 2.3, C‐reactive protein (CRP) level was 9.7 ± 13.2 mg/liter, and Bath Ankylosing Spondylitis Radiology Index for the spine (BASRI‐s) score was 1.7 ± 1.6. HRQOL was mainly associated with disease activity on univariate analysis (β values for BASDAI 0.646, patient global visual analog scale [VAS] 0.641, night back pain VAS 0.598, physician VAS 0.560, and CRP level 0.275; P < 0.01 for all), whereas the association with radiographic damage was weaker (standardized β for BASRI‐s 0.142; P < 0.05). On multivariate models, HRQOL only remained significantly associated with disease activity (standardized β for BASDAI 0.330; P < 0.01, and physician VAS 0.205 and night back pain VAS 0.210; P = 0.01). Similarly, physical function was associated with disease activity and radiographic damage on univariate analysis, but only with disease activity (BASDAI β 0.466; P < 0.01) on multivariate analysis. However, spinal mobility was associated with radiographic damage in both univariate and multivariate analyses. Conclusion: Patients with axial SpA already have impaired quality of life and physical function, albeit mildly, at the beginning of their disease course. Both outcomes are mainly associated with disease activity in these patients.